Development of Augmented Reality-Based Learning Media with Multi-Marker Feature on Biology Material for Highschool And Vocational School Students - Muh. Ihsan Zulfikar (PT. Lontara Digitech Indonesia, 2025)
This study aims to develop an augmented reality (AR) learning media named AR Biology, designed to enhance biology learning through 3D visualization and interactive multimedia. The application displays 3D objects and animations when a marker or image target is scanned, accompanied by synchronized audio and textual explanations. The novelty of this research lies in the implementation of a multi-marker feature that allows the visualization of combined 3D objects when two or more markers are brought close together. The research follows the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Trials conducted with 30 high school teachers and 20 vocational school students from grades X–XI demonstrated that AR Biology improved comprehension of biological concepts through interactive visualization. Expert validation categorized the application as “very feasible,” while user responses showed strong positive feedback, especially for the multi-marker feature that illustrates relationships among biological systems.